1991
DOI: 10.1152/ajpheart.1991.261.4.h1005
|View full text |Cite
|
Sign up to set email alerts
|

Positive inotropism in hypothermia partially depends on an increase in maximal Ca(2+)-activated force

Abstract: We investigated the contribution of maximal Ca(2+)-activated force to the positive inotropism induced by mild hypothermia. Phosphorus-31 nuclear magnetic resonance spectroscopy revealed that neither energy-related phosphorus compounds in myocardium nor intracellular pH was responsible for the change in contractility. Maximal Ca(2+)-activated pressure (MCAP), the intact-heart correlate of maximal Ca(2+)-activated force, was determined in isolated perfused rabbit hearts by measuring isovolumic left ventricular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 0 publications
3
27
0
1
Order By: Relevance
“…The observation that hypothermia caused a marked increase in contraction amplitude is supported by many other studies (32,34,36). Some investigators have suggested that an increase in myofilament Ca 2ϩ sensitivity is responsible, at least in part, for the increase in contraction amplitude associated with hypothermia (26,30). However, we found that the hypothermia-induced increase in contractions was accompanied by a proportional increase in the size of Ca 2ϩ transients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The observation that hypothermia caused a marked increase in contraction amplitude is supported by many other studies (32,34,36). Some investigators have suggested that an increase in myofilament Ca 2ϩ sensitivity is responsible, at least in part, for the increase in contraction amplitude associated with hypothermia (26,30). However, we found that the hypothermia-induced increase in contractions was accompanied by a proportional increase in the size of Ca 2ϩ transients.…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, cooling reduces the activity of the SR Ca 2ϩ -ATPase but increases SR Ca 2ϩ load in rabbit, ferret, and cat myocytes (32). Myofilament Ca 2ϩ sensitivity increases in response to cooling in intact rabbit hearts (26,31) but declines with cooling in chemically skinned rabbit ventricular muscle (21,22). Thus temperature has a marked influence on many components of the EC-coupling pathway in the mammalian heart.…”
mentioning
confidence: 99%
“…The slowed Ca 2ϩ handling not only decelerates but also prolongs contraction (Q 10 around 3) (4,22). Cooling enhances the Ca 2ϩ responsiveness so that contractile force increases for a given sarcoplasmic Ca 2ϩ concentration (12). Cooling suppresses myosin ATPase and hence cross-bridge cycling, leading to a slower contraction and relaxation (4)(5)(6)14).…”
Section: Discussionmentioning
confidence: 99%
“…22 Interrelated ionic disturbances underlie hypothermiainduced Ca 2ϩ loading during HS and dysfunction associated with Ca 2ϩ overloading on reperfusion. [25][26][27][28][29][30][31][32][33] Hypothermia most likely prolongs Ca 2ϩ channel influx and alters ion exchangers that trigger enhanced SR Ca 2ϩ -induced Ca 2ϩ release. During hypothermia, depressed Ca and Na pump activities may lead to Na and Ca overload via Na-H exchange and reversed Na-Ca exchange.…”
Section: Discussionmentioning
confidence: 99%